India’s Withdrawal from Regional Comprehensive Economic Partnership (RCEP) - Wicaksono, Abraham Hugo Pandu (Nation State: Journal of International Studies, 2021)
The Sino-US competition in the Indo-Pacific has become a central issue in international relations and how the competition of both countries affects state behavior. This article attempts to provide explanations of India's behavior in deciding to leave the Regional Comprehensive Economic Partnership (RCEP) agreement by using the neoclassical realism theory. Neoclassical realism believes that the actors' behavior is influenced by the constellation of international structures and domestic constellations. India's exit from RCEP was influenced by structural changes in the Indo-Pacific region, with the loss of China's balance of power marked by the withdrawal of the United States from the Trans-Pacific Partnership (TPP). Moreover, the condition has been exacerbated by the pressure received by Narendra Modi at the domestic level with the emergence of rejection of India's involvement in RCEP. It has influenced Narendra Modi's perception, who was active in the region with the two factors above, decided to resign from RCEP.